Communication Strategy In Agrotourism In Curup Village Rejang Lebong Regency Bengkulu - Yuliati Yuliati (Jurnal Ilmu Komunikasi, 2018)
The purpose of this study was to determine the marketing strategy of agrotourism marketing, in the Curup village of Rejang Lebong Regency, Bengkulu, by using the concept of integrated marketing communication. Rejang Lebong Regency, Bengkulu, in the last two years, many new tourist spots have emerged with the concept of agrotourism whose management is still individual. The study was conducted using a qualitative descriptive approach. The informant selection uses purposive sampling technique. The data conclusion technique used is observation, interviews, and literature study. Data validity test used is source triangulation. The results of this study are that from the general condition of tourism in Rejang Lebong Regency has experienced development every year. Agrotourism potential in this area is very potential to be developed. The marketing communication strategy that has been carried out by agrotourism in the Rejang Lebong Regency of Bengkulu is by utilizing social media Facebook as a form of promotional activities. Facebook is a owned media, which is social media that is managed by agrotourism managers in the form of status posts, photos, videos, visitor testimonials and live broadcasts. But in Facebook management it is still not maximal, sometimes in a few months no information is posted on its Facebook status. This is because the management of agrotourism is still an individual, a family business and that manages only the owner, there are no employee..